2012
DOI: 10.1074/mcp.m111.010199
|View full text |Cite
|
Sign up to set email alerts
|

Fast Multi-blind Modification Search through Tandem Mass Spectrometry

Abstract: With great biological interest in post-translational modifications (PTMs), various approaches have been introduced to identify PTMs using MS/MS. Recent developments for PTM identification have focused on an unrestrictive approach that searches MS/MS spectra for all known and possibly even unknown types of PTMs at once. However, the resulting expanded search space requires much longer search time and also increases the number of false positives (incorrect identifications) and false negatives (missed true identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
177
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(180 citation statements)
references
References 44 publications
1
177
0
2
Order By: Relevance
“…For example, although BSA and chicken transferrin gave similarly high numbers for both cross-linking chemistries, the coverage for catalase was much more extensive for the AXL approach (25 vs. 3). In addition to identifying cross-linked peptides by xQuest, we also performed additional data analysis using the unrestricted modification search engine, MOD a (32), which confirmed that the cross-linking chemistry was exclusively specific to Asp and Glu residues ( Fig. S3 and Dataset S2).…”
Section: Results For Model Proteins and Comparison With Lysine-lysinementioning
confidence: 67%
“…For example, although BSA and chicken transferrin gave similarly high numbers for both cross-linking chemistries, the coverage for catalase was much more extensive for the AXL approach (25 vs. 3). In addition to identifying cross-linked peptides by xQuest, we also performed additional data analysis using the unrestricted modification search engine, MOD a (32), which confirmed that the cross-linking chemistry was exclusively specific to Asp and Glu residues ( Fig. S3 and Dataset S2).…”
Section: Results For Model Proteins and Comparison With Lysine-lysinementioning
confidence: 67%
“…SEUEST and MASCOT were used first to evaluate the quality of the raw file and 75.48% of peptides were identified in HMGB1 protein sequence. ProteinProspect and MODa were used for unrestricted modification searching, and the coverage was 86.0% by blind searching (Na et al, 2012). In the results of unrestriced modification searching, methylation appeared four times in cancer group and was absent in adjacent group.…”
Section: High Mobility Group Box 1 Protein Is Methylated and Trmentioning
confidence: 99%
“…Selecting a database that does not contain the protein in question will result in the protein going undetected, while choosing a database that contains too much data can result in a large amount of false positives Everett et al 2010;Na et al 2012;Bern and Kil 2011), similar to the effect encountered when using error-tolerant searches (Creasy and Cottrell 2002). Numerous sequence databases are available, ranging from small home-grown databases to the centralized and well-annotated species-wide databases like UniProt (UniProt Consortium 2010), Ensembl (Flicek et al 2011) and NCBI nr (Pruitt et al 2007).…”
Section: From Acquired Data To Processed Resultsmentioning
confidence: 99%